An Analysis of Languagae Disorder in “Fly Away” (2011) Movie - Eva Meidi Kulsum; Aliya Nurdayani; Ayang Winda Sri Widianingsih; Rina Mutiarawati (Gunung Djati Conference Series, 2024)
Language disorder is the most frequent developmental disorder in childhood and it has a significant negative impact on children’s development. There are several types of language disorders that can be detected early, one of them is autism. This study aims to examine language disorder in a movie which focuses on one of the characters that shows Autism-Spectrum Disorder (ASD) symptoms. The method used in this research is qualitative analysis method by collecting data through movies. This study analysis was conducted on Mandy's character in the movie "fly away". The results of the study are then categorized, analyzed and concluded based on the underlying theories. It can be concluded that Mandy shows the characteristics of the ASD symptom in the form of echolalia, metaphorical language, neologisms and do not elicit prosody. Additionaly, it is hoped that this research can increase families’ awareness on early diagnosis that enables them to access appropriate support services, educational resources, and community programs, facilitate better coping mechanisms, reduce parental stress, and increase adult independence